In the coordinate plane, is a point on the ellipse: .
Let's make two tangent lines passing to the circle: , and are tangency points of the lines and circle. Find the range of .
The range can be expressed as . Submit .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let's look at the ellipse: 4 x 2 + 3 y 2 = 1 . It's semi-axis's are a = 2 , b = 3 , which means the focal distance is c = a 2 − b 2 = 4 − 3 = 1 . So, the point F ( − 1 , 0 ) is either a focal point of the ellipse and a center of the circle:
The circle is fully inside the ellipse because the closest point of the ellipse to point F is a − c = 1 far. That means, ∣ ∣ ∣ P F ∣ ∣ ∣ varies from 1 to 3 .
Now let's consider the tangent lines, A P and B P :
Since they are tangent from the same point, they are perpendicular to the radii, A F and B F , and A P = B P . That means triangles △ A P F and △ B P F are equal. So, ∠ A P B = ∠ A P F + ∠ F P B = 2 ∠ A P F .
Let P F = d and ∠ A P F = α , then:
∣ ∣ ∣ P F ∣ ∣ ∣ 2 = ∣ ∣ ∣ A F ∣ ∣ ∣ 2 + ∣ ∣ ∣ P A ∣ ∣ ∣ 2 d 2 = 1 + ∣ ∣ ∣ P A ∣ ∣ ∣ 2 ∣ ∣ ∣ P A ∣ ∣ ∣ = 1 − d 2
cos α = ∣ ∣ ∣ P F ∣ ∣ ∣ ∣ ∣ ∣ P A ∣ ∣ ∣ = d d 2 − 1 cos α = 1 − d 2 1
cos ( 2 α ) = 2 cos 2 α − 1 cos ( 2 α ) = 1 − d 2 2
Let's derive the needed value:
P A ⋅ P B = cos ∠ A P B ∣ ∣ ∣ P A ∣ ∣ ∣ ∣ ∣ ∣ P B ∣ ∣ ∣ P A ⋅ P B = cos ( 2 α ) ∣ ∣ ∣ P A ∣ ∣ ∣ 2 P A ⋅ P B = ( 1 − d 2 2 ) ( 1 − d 2 ) P A ⋅ P B = d 2 − 3 + d 2 2
Now we can find the range, knowing d ∈ [ 1 , 3 ] . Let's find the derivative:
∂ d ∂ ( P A ⋅ P B ) = 2 d − d 3 4
2 d − d 3 4 = 0 2 d 4 = 4 d = 2 4 1
So we've got:
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ ∂ d ∂ ( P A ⋅ P B ) < 0 , 1 ≤ d < 2 4 1 ∂ d ∂ ( P A ⋅ P B ) = 0 , d = 2 4 1 ∂ d ∂ ( P A ⋅ P B ) > 0 , 2 4 1 < d ≤ 3
That means minimum is reached at d = 2 4 1 and the maximum is at one of the ends of the interval, d = 1 or d = 3 :
P A ⋅ P B d = 2 4 1 = 2 − 3 + 2 = 2 2 − 3 P A ⋅ P B d = 1 = 1 − 3 + 2 = 0 P A ⋅ P B d = 3 = 9 − 3 + 9 2 = 9 5 6
So, l = 2 2 − 3 and r = 9 5 6 and the final answer is 6 0 5 0 6